Granule cell dispersion in two mouse models of temporal lobe epilepsy and reeler mice is associated with changes in dendritic orientation and spine distribution. Issue 7 (27th May 2022) - Puhahn‐Schmeiser, Barbara; Kleemann, Tobias; Jabbarli, Ramazan; Bock, Hans H.; Beck, Jürgen; Freiman, Thomas M.
Abstract: Temporal lobe epilepsy is characterized by hippocampal neuronal death in CA1 and hilus. Dentate gyrus granule cells survive but show dispersion of the compact granule cell layer. This is associated with decrease of the glycoprotein Reelin, which regulates neuron migration and dendrite outgrow. Reelin‐deficient (reeler) mice show no layering, their granule cells are dispersed throughout the dentate gyrus. We studied granule cell dendritic orientation and distribution of postsynaptic spines in reeler mice and two mouse models of temporal lobe epilepsy, namely the p35 knockout mice, which show Reelin‐independent neuronal migration defects, and mice with unilateral intrahippocampal kainate injection. Granule cells were Golgi‐stained and analyzed, using a computerized camera lucida system. Granule cells in naive controls exhibited a vertically oriented dendritic arbor with a small bifurcation angle if positioned proximal to the hilus and a wider dendritic bifurcation angle, if positioned distally. P35 knockout‐ and kainate‐injected mice showed a dispersed granule cell layer, granule cells showed basal dendrites with wider bifurcation angles, which lost position‐specific differences. Reeler mice lacked dendritic orientation. P35 knockout‐ and kainate‐injected mice showed increased dendritic spine density in the granule cell layer. Molecular layer dendrites showed a reduced spine density in kainate‐injected mice only, whereas in p35 knockouts no reduced spine density was seen. Reeler mice showed a homogenous high spine density. We hypothesize that granule cells migrate in temporal lobe epilepsy, develop new dendrites which show a spread of the dendritic tree, create new spines in areas proximal to mossy fiber sprouting, which is present in p35 knockout‐ and kainate‐injected mice and loose spines on distal dendrites if mossy cell death is present, as it was in kainate‐injected mice only. These results are in accordance with findings in epilepsy patients.